Xylometazoline and oxymetazoline - unusual effects of everyday drugs (literature review) - Jakub Klas; Natalia Kluz; Klaudia Piwowar (Kazimierz Wielki University, 2021)
The aim of the study is to systematize the knowledge about xylometazoline and oxymetazoline - commonly used nasal sprays with sympathicomimetic effect, mainly directly on α-adrenergic receptors [1]. A review of recent reports on possible side effects and new therapeutic options will be presented. Results: Over several years, reports have been published regarding descriptions of unusual cases of side effects, such as angina attack [4], a case of respiratory failure in a newborn [5], ischemic stroke [6], or anaphylactic reaction during routine surgery. In experiments using rats, on the other hand, it has been shown that these substances can also cause increased inflammation of the lower respiratory tract [7], as well as numerous ophthalmic problems [8]. Recent reports also suggest new uses for xylometazoline and oxymetazoline. In combination with lidocaine, an intranasal solution of xylometazoline has shown efficacy in the anesthesia of maxillary teeth in patients with minor carious lesions [9], and a beneficial therapeutic combination of oxymetazoline and dye laser (PDL) has also been reported for the treatment of rosacea, among others [10]. Conclusions: Although imidazoline derivatives were admitted to the drug list decades ago, still their pharmacological potential has not been fully exploited. Finding applications of these drugs in dermatology and dentistry may not only improve the efficacy and comfort of treatment, but also significantly reduce the costs of the whole therapy. The aforementioned reports on the side effects of xylometazoline and oxymetazoline should not be forgotten. It is possible that the presented examples will increase awareness to use these drugs with more respect, according to the recommendations on the leaflet.